Evaluation of Vaso-Occlusive Crisis Management with Patient Controlled Analgesia in Children with Sickle Cell Disease Requiring Admission. (18th May 2018) - Arbitre, Claire; Trottier, Evelyne D; Pastore, Yves; Bailey, Benoit; Robitaille, Nancy; Kleiber, Niina; Bergeron, Marie Joelle Dore; Villeneuve, Edith
Abstract: BACKGROUND: Vaso-occlusive crisis (VOC) is one of the most distressing occurrences in patients with sickle cell disease (SCD). Patient controlled analgesia (PCA) is recommended by NIH and expert opinions favor its early use. OBJECTIVES: We aim to review the use of PCA in patients with VOC and to evaluate if its early use is associated with faster pain control and reduced length of stay (LOS). DESIGN/METHODS: This retrospective single center study included all paediatric patients admitted and treated with PCA for a severe VOC from 2010 to 2016. "Early" use was defined as start of PCA within 48 hours of arrival in the emergency department (ED) and "late" use after 48 hours. Time to reach adequate analgesia was defined as OUCHER, verbal scale or Faces Pain Scale < 5/10 obtained twice consecutively in a 4-hours interval. Time to reach adequate analgesia and LOS were compared between early-PCA and late-PCA groups. RESULTS: A total of 46 patients presented 87 episodes of VOC treated with PCA during the study. Sixty-one episodes (70%) were treated with early-PCA and 26 (30%) with late-PCA. Both groups were comparable in terms of age (13.2 vs 12.8 years old), gender (55.8% female vs 57.7%), hemoglobin phenotype (80.3% HbSS vs 76.9%), but median pain score at admission was higher in early-PCA than in late-PCA (9/10 vs 7/10, median difference 1 (95% CI 0, 2). Early-PCA was associated with a median reduction in LOS of 3.15 days (95% CI 1.65, 4.82) (median early-PCA LOS 6.4 vs late-PCA 10.0 days). Time to reach analgesia could be evaluated only in a subset of patients (20 in early-PCA and 12 in late-PCA group). Although time to reach adequate analgesia tended to be shorter in the early-PCA group, it was not statistically different: median102.9 hours vs 123.5 hours, difference of 30.4 (95% CI -4.0, 72.5). Side effects were observed during 29 (33.3%) PCA treatments (19/61 (31.2%) episodes in early-PCA, 10/26 (38.5%) in late-PCA group) among which 16 (18.6%) were significant adverse events. These were observed in 15 patients who required interventions: 2 desaturations requiring oxygen without intubation, 8 neurologic abnormalities (hallucinations, visual abnormalities, no stroke), 6 urinary retentions. CONCLUSION: Early use of PCA for severe VOC was associated with a reduced length of hospital stay despite that these patients had higher pain score on admission. Prospective studies are needed to support these positive outcomes.